2016
DOI: 10.1155/2016/8469357
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Production of Short Chain Fatty Acids from Lignocellulosic Biomass: Current Processes and Market

Abstract: Biological production of organic acids from conversion of biomass derivatives has received increased attention among scientists and engineers and in business because of the attractive properties such as renewability, sustainability, degradability, and versatility. The aim of the present review is to summarize recent research and development of short chain fatty acids production by anaerobic fermentation of nonfood biomass and to evaluate the status and outlook for a sustainable industrial production of such bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(61 citation statements)
references
References 109 publications
(91 reference statements)
0
53
0
Order By: Relevance
“…The dependence of VFAs profile and concentration on the employed substrate and the operational conditions was previously reported in . Moreover, the differences in VFAs profile would determine the different specific application of each VFA . At psychrophilic conditions, pH 7.5 mediated higher acetic acid concentration (50–57%) compared with pH 5.5 (40–46%).…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…The dependence of VFAs profile and concentration on the employed substrate and the operational conditions was previously reported in . Moreover, the differences in VFAs profile would determine the different specific application of each VFA . At psychrophilic conditions, pH 7.5 mediated higher acetic acid concentration (50–57%) compared with pH 5.5 (40–46%).…”
Section: Resultsmentioning
confidence: 69%
“…25 Moreover, the differences in VFAs profile would determine the different specific application of each VFA. 26 At psychrophilic conditions, pH 7.5 mediated higher acetic acid concentration (50-57%) compared with pH 5.5 (40-46%). In both cases, acetic acid was the most abundant VFA ( Figure 3A-D).…”
Section: Effect Of Initial Ph and Temperature On Ad Of Protease Pretrmentioning
confidence: 91%
“…Biorefineries, in principle, work similarly to petrochemical refineries in that lignocellulosic biomass, which is a complex mixture containing sugars and aromatic components, are broken down into several high-value products [1]. Studies have also shown that certain functional groups added to naphtha in petrochemical refineries for the production of chemicals are usually naturally present in lignocellulosic biomass [2]. Also, the catalytic processing of petrochemical derivatives such as naphtha and syngas traditionally used for producing carboxylic acids involves high temperature and pressure conditions that result in high energy inputs [3].…”
Section: Introductionmentioning
confidence: 99%
“…Several routes have been developed for the conversion of lignocellulosic biomass to biofuels such as pyrolysis [8], gasification [9], liquefaction [10], and a combination of comparatively low-severity thermochemical pretreatment followed by concerted action of enzymes and microorganisms [11]. While each of these technologies has different merits and problems, as discussed in several reviews on their respective fields, the current state of the art in the latter platform is usually considered more specific and cost-efficient and results in high-value byproduct streams [2]. The biomass sugars obtained after thermochemical and enzymatic pretreatment have previously usually been converted to alcohols such as ethanol or butanol [12] and to a lesser degree anaerobically fermented to produce carboxylic acids for further catalytic upgrading to biofuels [13].…”
Section: Introductionmentioning
confidence: 99%
“…Anaerobic digestion is a well-known valorization method for complex waste materials and, for example, across Europe there are over 17,000 biogas plants (situation in the end of the year 2016; EBA, 2018). VFAs, for example, acetic acid, butyric acid, or lactic acid, are produced industrially with certain bacterial strains or pure cultures (Cavinato, Frison, et al, 2017), and the substrates suitable for these processes are usually simple molecules, for example, C5 and C6 sugars (Baumann & Westermann, 2016). The production of VFAs through mixed consortia fermentation can utilize more complex substrates in nonsterile conditions (Jankowska, Chwiałkowska, Stodolny, & Oleskowicz-Popiel, 2015;Jankowska, Duber, Chwialkowska, Stodolny, & Oleskowicz-Popiel, 2018).…”
mentioning
confidence: 99%